Evolution of Scales and Levels of Islam and Politics Analysis in Post-Soviet Russia - Mirzakhanov Dzhabrail Gasanovich; Magomedov Arbakhan Kurbanovich (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2015)
The article studies the basic and complicated evolution of different approaches for investigating Russian post-Soviet Islamic transformation. The authors describe the logic and dynamic of scrutinizing such kind of problems as Islamic consciousness and Muslim institutes, relationships between Islam and ethnic political develoments, forms and manifestations of Islamic fundamentalism. In an effort to identify and assess the signs of post-Soviet Islamic revival, the Russian academic community has obviously been driven to despair. Especially since the tragedy of 9/11/2001 as a source of studying Islam as an evasive object. The main goal of this paper is the methodological innovation which consists in multilayered approach. The authors argue that changes of parameters and structure of post-Soviet policy is reflected in the change of format and unities of analysis. The paper examines the character of academic discussion about different understanding of such political phenomena as politization of Islam as well as bordering Islam in terms of multi-level methodology. This methodology could be able to clarify very complicated Islamic features: socio-territorial organization, communication, and the reproduction channels. It alone will help us explain changing Islam as a social and political enigma. In this paper the authors have correctly identified the phenomenon of Muslim regionalization as a situation under which the Islamic leaders concentrate on religious development at the local level. It is not the authors’ aim to discuss the forms of Islamic existence and its religious-teaching component. The authors favor the wider approach typical of political science in which there is a component of Islamic studies. This analysis has demonstrated that the multi-layered approach to Islam, which identifies its viable segments, has a considerable heuristic potential. This approach helps to understand the inner dynamics of the Islamic development as a complex social and political phenomenon. This reconfirms the old truth that the deeper the analysis goes into the past the more integral an image of reality it acquires.